Glucose Regulation of Thrombospondin and Its Role in the Modulation of Smooth Muscle Cell Proliferation. (25th May 2010) - Maile, Laura A.; Allen, Lee B.; Hanzaker, Christopher F.; Gollahon, Katherine A.; Dunbar, Paul; Clemmons, David R.
Abstract : Smooth muscle cells (SMC) maintained in high glucose are more responsive to IGF-I than those in normal glucose. There is significantly more thrombospondin-1 (TSP-1) in extracellular matrix surrounding SMC grown in 25 mM glucose. In this study we investigated 1) the mechanism by which glucose regulates TSP-1 levels and 2) the mechanism by which TS-1 enhances IGF-I signaling. The addition of TSP-1 to primary SMC was sufficient to enhance IGF-I responsiveness in normal glucose. Reducing TSP-1 protein levels inhibited IGF-I signaling in SMC maintained in high glucose. We determined that TSP-1 protected IAP/CD47 from cleavage and thereby facilitated its association with SHP substrate-1 (SHPS-1). We have shown previously that the hyperglycemia induced protection of IAP from cleavage is an important component of the ability of hyperglycemia to enhance IGF-I signaling. Furthermore we determined that TSP-1 also enhanced phosphorylation of theβ 3 subunit of theα Vβ 3 integrin, another molecular event that we have shown are critical for SMC response to IGF-I in high glucose. Our studies also revealed that the difference in the amount of TSP-1 in the two different glucose conditions was due, at least in part, to a difference in the cellular uptake and degradation of TSP-1.